(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Geomorphological map is an essential tool for various types of planning and developmental activities in an area such as land use planning, agriculture, forestry, civil-engineering, exploration and utilization of mineral resources,groundwater development,terrain evaluation etc. The geogmorphological mapping for Ananthapur district area was carried out with the help of SENTINEL - 2A satellite(June 23rd 2018) Spatial Resolution 10m, Multispectral, Digital data imagery on 1:50,000 scale by visual interpretation techniques. Remote Sensing(RS) and Geographical Information Systems(GIS) play a basic employment in creating topical maps and incorporating examination for mapping, overseeing and observing the regular assets. RS and GIS innovations have propelled another period in the field of connected topography and geomorphology. Geomorphology is the exploration of landforms present on the Earth's surface and their deliberate examination is vital and special,keeping in mind the end goal to decipher them as marks of the past and continuous topographical procedures. The present examination intends to outline geomorphological highlights in the location of Ananthapur district in perspective of visual picture interpretation system. The examination territory principally contains Moderately Weathered Pediplain(39%) trailed by Shallow Weathered Pediplain(21%) and Structural Hill(16%).These maps would be helpful in further investigation for common earth assets arranging, administration and basic leadership. Topical maps of geomorphology have been produced on satellite information. Standard visual clarification strategies as per the norms given by NRSC have been pursued and depicted on-screen digitations of highlights.